1999
DOI: 10.1159/000029332
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Gas Exchange in Life-Long Nonsmoking Patients with Diabetes mellitus

Abstract: In a companion paper, we have found that the alveolar epithelial basal lamina, endothelial basal lamina and both fused were significantly thicker in 6 autopsied diabetics than in 6 control subjects. The purpose of the present work was to assess whether these lesions have detrimental effects on gas exchange. We investigated 20 life-long nonsmoking subjects: 10 healthy subjects and 10 insulin-dependent diabetics. All of them had one to four diabetic complications of the following organs: kidney, retina, nerves o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 15 publications
(17 reference statements)
0
12
0
1
Order By: Relevance
“…Autopsy findings in human diabetics have demonstrated the presence of a thickened alveolar epithelial and pulmonary capillary basal lamina [10, 11, 12]. On the other hand, Minette et al [13]found a normal transfer factor, transfer coefficient, oxygen consumption and arterial blood gases in 10 insulin-dependent patients. The data were collected at rest and during two levels of submaximal exercises [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Autopsy findings in human diabetics have demonstrated the presence of a thickened alveolar epithelial and pulmonary capillary basal lamina [10, 11, 12]. On the other hand, Minette et al [13]found a normal transfer factor, transfer coefficient, oxygen consumption and arterial blood gases in 10 insulin-dependent patients. The data were collected at rest and during two levels of submaximal exercises [13].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Minette et al [13]found a normal transfer factor, transfer coefficient, oxygen consumption and arterial blood gases in 10 insulin-dependent patients. The data were collected at rest and during two levels of submaximal exercises [13]. In the English literature, there are very few data concerning pulmonary function abnormalities in patients with type 2 diabetes mellitus (NIDDM).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies of lung function in diabetic subjects have shown slightly decreased indices of forced expiration, lung volumes and diffusion capacity in both type-1 [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] and type-2 diabetes [18][19][20][21][22][23][24]. Almost all of these studies are cross-sectional and include a small number of patients.…”
mentioning
confidence: 99%
“…In recent years it has been documented that alveolar epithelial and endothelial capillary basal laminae and both fused, are significantly thicker in autopsied patients with diabetes mellitus than in the control subjects [3,4]. Also several authors documented that even in patients lacking manifest pulmonary diseases, there are functional abnormalities in pulmonary gas exchange [5][6][7][8][9].…”
mentioning
confidence: 99%